ANALISIS KEEFEKTIFAN GOOGLE CLASSROOM DALAM PEMBELAJARAN DARING - Tri Hartatik; Djatmiko Hidajat; Annisa Prima Exacta (Universitas Veteran Bangun Nusantara, 2021)
This study aims to determine the level of effectiveness google classroom in online learning. This research uses quantitative methods through a google form questionnaire and is followed by quantitative descriptive data analysis. The population of this study were students of class XII SMA Veteran 1 Sukoharjo with a sample of 23 students from class XII BB. Based on the research, the average value of student learning outcomes was 79.348 with the high category. There were 21 students who completed and there were 2 people who had not completed or did not meet the completeness score of 70. The results of student responses after being distributed by the questionnaire via google form showed that the percentage value of student responses was 60.87% in the moderate category. Based on the results of research and discussion, the level of effectiveness of Google Classroom is quite effective for delivering material, delivering and collecting assignments.